IoT-driven sustainable green energy systems in an organization: Issues and challenges - Ajra, Husnul; Mazlina, Abdul Majid; Islam, Md. Shohidul; Azlee, Zabidi; Ismail Hammad, Khalid Adam (ISTES Organization, 2023)
Sustainable energy harvesting from renewable sources such as solar, wind, or water power leads to a significant challenge in managing IoT applications. Utilizing renewable energy combined with optimized system energy has become a major concern across IoT-based large-scale systems for obtaining a reliable and energy-efficient eco-infrastructure system. A green technology-operated IoT (G-IoT) has been introduced as part of energy efficiency solutions for IoT-based systems to address the aforementioned issues. Many researchers have explored various solutions related to energy-efficient G-IoT approaches for eco-infrastructure systems in an organization such as a university campus. As there are various existing approaches to G-IoT, the question here is how to produce a reliable, real-time, and energy-efficient system to ensure sustainability for replicating a city like a university. This paper intends to explore existing works on G-IoT-based approaches in terms of energy efficiency issues and challenges from various authors' perspectives. The key goal of this study is to conduct a comprehensive overview to identify the parameters involved in developing a real-time and energy-efficient G-IoT system from existing works. Accordingly, an operational approach is introduced to review and analyze the work, factors, and techniques of G-IoT-related existing articles. From exploration and analysis, this study affords an in-depth description based on current trends, related parameter identifications, and capable approaches to bridge existing strategic gaps for future research. Thus, this study is expected to develop an IoT-powered sustainable green energy system replica for an organization.